Intermediate Algebra for College Students (7th Edition)

Published by Pearson
ISBN 10: 0-13417-894-7
ISBN 13: 978-0-13417-894-3

Chapter 2 - Section 2.3 - The Algebra of Functions - Exercise Set - Page 133: 59



Work Step by Step

$f(1)=-6, g(1)=-3, f(-1)=3, g(-1)=-2$ $(f+g)(1)=f(1)+g(1)=-6+(-3)=-9$ $(g-f)(-1)=g(-1)-f(-1)=-2-3=-5$ $(f+g)(1)-(g-f)(-1)=-9-(-5)=-9+5=-4$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.